Platelet-derived growth factor (PDGF) in oncogenesis: development of a vascular connective tissue stroma in xenotransplanted human melanoma producing PDGF-BB. - Forsberg, K (1993)
Human WM9 melanoma cells, previously shown to be devoid of PDGF expression, were stably transfected with a PDGF-B cDNA under the transcriptional control of a cytomegalovirus promoter. Northern blot analysis revealed high expression of an mRNA of the expected size in the PDGF-B-transfected cells. Synthesis and secretion of PDGF-BB was confirmed by immunoprecipitation. Furthermore, conditioned medium from PDGF-B-transfected cells contained a mitogenic activity for fibroblasts. For analysis of tumor growth in vivo, cells of each type were injected subcutaneously into BALB/c nu/nu mice. Tumors from mice injected with WM9 cells transfected with the vector only contained large necrotic areas; only scant blood vessels with narrow lumina were observed. No connective tissue was present. In the tumors from PDGF-B-transfected WM9 cells, nests of tumor were divided by connective tissue septa. An abundance of blood vessels was observed in the connective tissue septa and within the tumor cell nests. There was a complete absence of necrosis in these tumors. The present results suggest that tumor-derived PDGF-BB is a potent mediator of connective tissue stroma formation. The connective tissue framework that is generated in response to PDGF-BB may form a solid support for newly formed blood vessels and, thereby, facilitate the formation of a functional vascular system in the tumor.